The effect of twin-to-twin delivery time intervals on neonatal outcome for second twins - L. Lindroos; A. Elfvin; L. Ladfors; U.-B. Wennerholm (BMC, 2018)
Abstract Background The objective was to examine the effect of twin-to-twin delivery intervals on neonatal outcome for second twins. Methods This was a retrospective, hospital-based study, performed at a university teaching hospital in Western Sweden. Twin deliveries between 2008 and 2014 at ≥32 + 0 weeks of gestation, where the first twin was delivered vaginally, were included. Primary outcome was a composite outcome of metabolic acidosis, Apgar < 4 at 5 min or peri/neonatal mortality in the second twin. Secondary outcome was a composite outcome of neonatal morbidity. Results A total of 527 twin deliveries were included. The median twin-to-twin delivery interval time was 19 min (range 2-399 min) and 68% of all second twins were delivered within 30 min. Primary outcome occurred in 2.6% of the second twins. Median twin-to-twin delivery interval was 34 min (8-78 min) for the second twin with a primary outcome, and 19 min (2-399 min) for the second twin with no primary outcome (p = 0.028). Second twins delivered within a twin-to-twin interval of 0-30 min had a higher pH in umbilical artery blood gas than those delivered after 30 min (pH 7.23 and pH 7.20, p <  0.0001). Secondary outcome was not associated with twin-to-twin delivery interval time. The combined vaginal-cesarean delivery rate was 6.6% (n = 35) and the rate was higher with twin-to-twin delivery interval >  30 min (p <  0.0001). Conclusions An association, but not necessarily a causality, between twin-to-twin delivery interval and primary outcome was seen. An upper time limit on twin-to-twin delivery time intervals may be justified. However, the optimal time interval needs further studies.